HUBUNGAN ANTARA KEMAMPUAN DASAR DAN PENGEMBANGAN KARIR DENGAN PRODUKTIVITAS KERJA PT MERLIN BANDUNG - Neneng Fauziah (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2015)
Connection between basic capacity and developing of career with productivity work labour at PT Merling Bandung.This research as a purpose to know as far as possible bussines to select labour based on basic capacity and how long a bussines developing of career to increase work labour productivity. From this research results were found that; (1) there is a connection between basic capacity with work productivities; (2) there is a connection between developing of career with work productivities; (3) there is a connection developing of career in a together with work productivities.